Technology of Machine Tools - F.Krar Steve (MC Graw Hill Glencoe, 1997)
This revised edition of the most widely used textbook in its field trains students to use conventional machine tools and introduces them to new and emerging manufacturing technologies and processes. It's written in an easy-to-understand style and features more than 1,000 line drawing and 500 photographs.